INSILICO IDENTIFICATION OF SUITABLE ANTAGONISTS FOR GLYCOGEN SYNTHASE KINASE (GSK-3BETA) IN ALZHEIMER’S DISEASE - K. YELLAMMA; K. PRAVEEN; K. PEERA (International Journal of Pharma and Bio Sciences, 2014)
Alzheimer’s disease is also caused by the formation of β Amyloid Plaques and Neurofibrillary Tangles (NFT) due to structural changes in Tau protein. Recent studies have implicated molecular and cellular signaling cascades of Serine Threonine Kinase and Glycogen Synthase Kinase 3β (GSK-3β) in pathogenesis of AD. GSK-3β plays an important role in the formation of NFT and senile plaques in AD. In view of this, the present study focused on identification of GSK-3β inhibitors. The interaction between GSK-3β and selected analogues have studied with modern bioinformatics programs to indentify the best lead molecule, which strongly binds to the active site of the GSK-3β and inhibits its biological activity. The results observed that among 27 Indirubin analogues docked against GSK-3β, Isoindigotin &Indirubin-3-monoxime showed best affinity with GSK-3β than others, Isoindigotin exhibited best biological activity. Therefore, it is suggested that Indirubin analogues controls biochemical process involved in formation of NFT in AD.